PENERAPAN METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS MENGAJAR GURU DI SMA - M. Isnando Tamrin; Sri Hartati (Ensiklopedia of Journal, 2023)
The goal to be achieved in this research is to find out the application of the Islamic Religious Education (PAI) learning method in improving the teaching quality of teachers at SMA Negeri 1 Ulakan Tapakis, Padang Pariaman Regency. This type of research is a qualitative descriptive research with a case study approach. The subjects of this study were PAI teachers and school principals. Data collection techniques used are observation, interviews and documentation. The data analysis technique used is Milles and Huberman's qualitative technique. The results showed that Islamic Religious Education teachers at SMAN 1 Ulakan Tapakis, Padang Pariaman Regency, in the learning process of Islamic Religious Education did not use just one method, but Islamic Religious Education teachers used a variety of methods, namely how to mix several methods in a learning activity to complement each other's existing weaknesses. in this method so that it becomes more effective and efficient. The methods are lecture, discussion, question and answer, discussion and assignment methods.